Dostoevsky beyond Dostoevsky Science, Religion, Philosophy - Evdokimova, Svetlana; Golstein, Vladimir (Academic Studies Press, 2016)
Dostoevsky beyond Dostoevsky is a collection of essays with a broad interdisciplinary focus. It includes contributions by leading Dostoevsky scholars, social scientists, scholars of religion and philosophy. The volume considers aesthetics, philosophy, theology, and science of the 19th century Russia and the West that might have informed Dostoevsky's thought and art. Issues such as evolutionary theory and literature, science and society, scientific and theological components of comparative intellectual history, and aesthetic debates of the nineteenth century Russia form the core of the intellectual framework of this book. Dostoevsky's oeuvre with its wide-ranging interests and engagement with philosophical, religious, political, economic, and scientific discourses of his time emerges as a particularly important case for the study of cross-fertilization among disciplines.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Literary Criticism / Russian & Former Soviet Union; Literature -- History and criticism; Electronic books